PERMAINAN PUZZLE MEMPENGARUHI PERKEMBANGAN KECERDASAN VISUAL-SPATIAL ANAK USIA 4-5 TAHUN DI TK AL-FATH DESA KEBOAN ANOM GEDANGAN SIDOARJO - Devi Ayu Anjani; Siti Nurjanah (Jurnal Ilmiah Kesehatan, 2014)
One of the Visual-spatial intelligence development of children aged 4-5 years is a child can recognize up to 12 kinds of colours, in fact it is still found children aged 4-5 are not able to recognize colours properly. From preliminary data obtained 35.4% of children aged 4-5 years in visual-spatial intelligence development of children, they were not able to recognize colours properly. The purpose of this study was to determine the effect of a puzzle game on visual-spatial intelligence development of children aged 4-5 years. This study was conducted in Al-Fath kindergarten. Study design use pre experimental with one group pretest-posttest design. The population were children aged 4-5 years in kindergarten Al-Fath by 150 children with 30 respondents taken by simple random sampling. Independent variable is puzzle game and the dependent variable is the development of children's visual-spatial intelligence. Data were collected use observation sheets then analyzed by statistically test of paired sample t test with significance level a <0.05.The results showed there is an increasing (13.4%) very good and (20%) good of visual-spatial intelligence after giving intervention. Obtained r = 0.000 < a = 0.05 so rejected, which means there is a puzzle game influence on the development of visual-spatial intelligence of children aged 4-5 years in kindergarten Al-Fath Keboan Anom village Gedangan Sidoarjo.From study results concluded that the puzzle can be used as a medium of learning to improve children's visual-spatial intelligence. It is recommended to use puzzle and parents can facilitate educational games for children and accompany them.